Adaptation of the Perception of Using E-learning Platforms Scale in the Scope of Technology Acceptance Model and Its Examination in Relation to Different Variables - Üzümcü, Özlem; Sıvacı, Seda; Hakkoymaz, Sakine (Fırat University, 2024)
With the rapid advancement of technology, learning environments have also found a significant place in the digital world. The widespread adoption of e-learning platforms has triggered a major transformation in higher education, necessitating an understanding of the factors influencing their acceptance by students. This study aims to investigate higher education students' perceptions of e-learning platforms based on various variables. For this purpose, he Perception of Using E-learning Platforms Scale in the Scope of Technology Acceptance Model (TAM) consisting of 46 items and ensuring a good fit to the data in terms of structural validity, was adapted to the Turkish context. Subsequently, using the adapted scale, participants' perceptions of using e-learning platforms and the scores obtained from the scale's sub-dimensions were examined, considering different variables. Confirmatory factor analysis with the collected data revealed that the scale maintains a valid five-factor structure, as in its original form. Additionally, the calculated Cronbach's alpha values indicate the reliability of the scale. While participants' perceptions of using e-learning platforms and scores from the scale's sub-dimensions did not show a significant difference based on gender and department, a meaningful differentiation was observed concerning class level. The findings are discussed in the context of relevant literature.

Teknolojinin hızla ilerlemesiyle birlikte öğrenme ortamları da dijital dünyada önemli bir konum kazanmıştır. E-öğrenme platformlarının yaygınlaşması, yükseköğretimde önemli değişikliklere yol açmış ve bu platformların öğrenciler tarafından benimsenmesini etkileyen faktörlerin anlaşılmasını gerektirmiştir. Bu çalışma, yükseköğretim öğrencilerinin e-öğrenme platformlarına yönelik algılarını farklı değişkenler temelinde araştırmayı amaçlamaktadır. Bu amaç doğrultusunda, yapı geçerliliği açısından verilere iyi uyum sağlayan, 46 maddeden oluşan Teknoloji Kabul Modeli (TKM) kapsamında E-Öğrenme Platformlarının Kullanım Algısı Ölçeği Türkçeye uyarlanmıştır. Daha sonra uyarlanan ölçek kullanılarak katılımcıların e-öğrenme platformlarını kullanım algıları ve ölçeğin alt boyutlarından aldıkları puanlar, farklı değişkenler göz önünde bulundurularak incelenmiştir. Toplanan verilerle yapılan doğrulayıcı faktör analizi, ölçeğin orijinalinde geçerli olan beş faktörlü bir yapıya sahip olduğunu göstermiştir. Ayrıca hesaplanan Cronbach alfa ve McDonald’s Omega değerleri, ölçeğin güvenilir olduğunu ortaya koymaktadır. Katılımcıların e-öğrenme platformlarını kullanım algıları ve ölçeğin alt boyutlarından aldıkları puanlar, cinsiyet ve bölüme göre anlamlı bir farklılık göstermezken, sınıf düzeyine göre yapılan incelemede anlamlı bir şekilde farklılaştığı tespit edilmiştir. Sonuçlar, ilgili alanyazın bağlamında tartışılmıştır.
TEKNOLOJİ KABUL MODELİ KAPSAMINDA E-ÖĞRENME PLATFORMLARININ KULLANIM ALGISI ÖLÇEĞİNİN UYARLANMASI VE FARKLI DEĞİŞKENLERE GÖRE İNCELENMESİ
Keywords: Information Systems User Experience Design and Development; Bilgi Sistemleri Kullanıcı Deneyimi Tasarımı ve Geliştirme